2016
DOI: 10.1002/2016gl070669
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale enhancement in aerosol absorption in the lower free troposphere over continental India during spring

Abstract: Aerosol absorption in the lower troposphere over continental India was assessed using extensive measurements of the vertical distribution of absorption coefficients aboard an instrumented aircraft. Measurements were made from seven base stations during winter (November–December 2012) and spring (April–May 2013), supplemented by the data from the networks of surface observatories. A definite enhancement in aerosol absorption has been observed in the lower free troposphere over the Indo‐Gangetic Plain (IGP) duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 27 publications
5
17
0
Order By: Relevance
“…A constant volumetric flow of 70 LPM (liters per minute) was maintained using an external pump connected to the main inlet assembly, which provided iso-kinetic flow for the average speed of 300 km/hr maintained by the aircraft during the entire campaign. The efficiency of this inlet system has been already proven in several previous campaigns (Gogoi et al, 2019;Nair et al, 2016;Babu et al, 2016).…”
Section: Study Region and Flight Detailsmentioning
confidence: 84%
See 2 more Smart Citations
“…A constant volumetric flow of 70 LPM (liters per minute) was maintained using an external pump connected to the main inlet assembly, which provided iso-kinetic flow for the average speed of 300 km/hr maintained by the aircraft during the entire campaign. The efficiency of this inlet system has been already proven in several previous campaigns (Gogoi et al, 2019;Nair et al, 2016;Babu et al, 2016).…”
Section: Study Region and Flight Detailsmentioning
confidence: 84%
“…The measurements were carried out aboard the instrumented aircraft (Beechcraft-200) fitted with an iso-kinetic inlet, mounted (front facing) at the bottom of the fuselage for aspirating ambient aerosols and detailed in a few earlier papers (Babu et al, 2016;Vaishya et al, 2018;Gogoi et al, 2019). A constant volumetric flow of 70 LPM (liters per minute) was maintained using an external pump connected to the main inlet assembly, which provided iso-kinetic flow for the average speed of 300 km/hr maintained by the aircraft during the entire campaign.…”
Section: Study Region and Flight Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…Examining the vertical profile of aerosols over Bangalore (an urban station in the southern part of India) using a groundbased micro-pulse lidar, Satheesh et al (2006) have reported morning-time (nighttime) vertical lifting (confinement) of aerosols during summer days. Carrying out airborne measurements of BC and absorption coefficients over several stations across India, Babu et al (2008Babu et al ( , 2010 and Nair et al (2016) have reported a near-steady vertical distribution up to an altitude of 3 km above the ground with isolated peaks of higher BC concentration and absorption coefficients during the pre-monsoon period above most of the landmass. Synthesising multi-platform measurements, Satheesh et al (2008) have revealed the existence of elevated aerosol layers in the middle troposphere (4-5 km).…”
Section: Introductionmentioning
confidence: 99%
“…With this backdrop, a few studies have examined the vertical distribution of aerosols (extinction coefficient values and/or BC mass concentration values) over the Indian region using multiple observational platforms, such as ground-based (Satheesh et al, 2006), airborne or space-based lidar Prijith et al, 2016), instrumented aircraft (Moorthy et al, 2004;Babu et al, 2008Babu et al, , 2010Nair et al, 2016) and tethered and high-altitude balloons (Babu et al, 2011). Carrying out such observations for the first time over India, Moorthy et al (2004) noticed an exponential decrease in BC concentration within the boundary layer and a steady value above it over an urban station (Hyderabad) in south-central India during February 2004.…”
Section: Introductionmentioning
confidence: 99%